A prohibition of recording patients without prior consent – is it still a case? – some comments on the judgment of the Supreme Administrative Court of May 23, 2023, II OSK 1761/20 - Adrych-Brzezińska, Izabela (Studia Iuridica Toruniensia, 2024)
The Supreme Administrative Court, in its judgment of May 23, 2023, in the case No. II OSK 1761/20, dismissed the cassation against the judgment of the Provincial Administrative Court in Warsaw, while the last court previously dismissed the complaint against the decision of the Commissioner for Patient’s Rights regarding the recognition of the practice as violating the collective rights of patients. The decision was issued in connection with the audio and video recording of the patients while providing health services without their prior consent. This paper is an analysis of the position adopted by the court through the prism of the applicable and recently amended provisions in this area. The paper also indicates numerous legal implications related to the possibility of recording the process of providing health services, which were omitted in the cited judgment.